Control of Charge Dynamics via Use of Nonionic Phosphonate Chains and Their Effectiveness for Inverted Structure Solar Cells. Issue 18 (14th July 2015) - Kim, Gyoungsik; Song, Seyeong; Lee, Jungho; Kim, Taehyo; Lee, Tack Ho; Walker, Bright; Kim, Jin Young; Yang, Changduk
<x xml:space="preserve">Abstract</x> Considering that a high compatibility at hybrid organic/inorganic interfaces can be achieved using polar and hydrophilic functionalities, this approach is used to improve inverted polymer solar cell performance by introducing nonionic phosphonate side chains (at 0%, 5%, 15%, and 30% substitution levels) into a series of isoindigo‐based polymers (PIIGDT‐Pn). This approach led to ≈20% improvement in power conversion efficiency compared to a nonmodified control polymer, via an increased short‐circuit current (JSC). This enhancement is believed to stem from reduced nongerminate recombination and improved charge carried extraction when the level of phosphonate substitution is optimized. These results are substantiated by a combination of detailed electrical measurements including space‐charged limited current modeling, light intensity–dependent photocurrent (Jph) analysis, and morphological studies (grazing‐incidence wide‐angle X‐ray scattering and atomic force microscopy). This is the first practical report demonstrating the use of nonionic polar side chains to control charge carrier dynamics in an existing photovoltaic polymer structure. It is envisioned that this simple strategy may be applied to other material systems and yield new materials with the potential for even higher performance.